2003
DOI: 10.1080/03079450310001610631
|View full text |Cite
|
Sign up to set email alerts
|

Increased lymphocyte subpopulations and macrophages in the ovaries and oviducts of laying hens infected withSalmonella entericaserovar Enteritidis

Abstract: Salmonella enterica serovar Enteritidis (SE) is a causative agent for human food poisoning cases throughout the world. The ovaries and the oviducts of the laying hens are the major sites of SE colonization from which vertical transmission to eggs occurs. In this study, Salmonella-induced changes in T lymphocytes, B lymphocytes and macrophages in the ovaries and oviducts were assessed after primary and secondary experimental inoculations of laying hen with SE. Statistically significant increases in the numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…For CD8 + cells, we found an increase after the Salmonella infection in both chicken lines, but faster in time post infection in line F. An increase in the amount of CD8 + cells was also found in the caeca after a Salmonella infection [1,6], but also decreases in the amount of CD8+ cells in the caeca are reported [18]. In the oviduct of laying hens, the numbers of CD8 + cells were increased after a Salmonella infection [4,25,26]. Our and other results suggest that differences in influx of T-cell subpopulations after a Salmonella infection are dependent on the location in the digestive tract, infection dose, time post infection, age at the time of infection and genetic background of the chickens.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…For CD8 + cells, we found an increase after the Salmonella infection in both chicken lines, but faster in time post infection in line F. An increase in the amount of CD8 + cells was also found in the caeca after a Salmonella infection [1,6], but also decreases in the amount of CD8+ cells in the caeca are reported [18]. In the oviduct of laying hens, the numbers of CD8 + cells were increased after a Salmonella infection [4,25,26]. Our and other results suggest that differences in influx of T-cell subpopulations after a Salmonella infection are dependent on the location in the digestive tract, infection dose, time post infection, age at the time of infection and genetic background of the chickens.…”
Section: Discussionmentioning
confidence: 53%
“…Also in mice the number of CD4 + T-cells increased in the gut following Salmonella challenge [2,15]. Furthermore in the ovary and oviduct of laying hens, increased numbers of CD4 + T-cells were reported after a Salmonella infection [4,25,26]. However, for the early host response CD4 + or CD8 + T-cells are probably not required [14].…”
Section: Discussionmentioning
confidence: 99%
“…An increased level of IL-1β stimulates infiltration of T cells and macrophages [42]. Treatment of birds with SE causes infiltration of these immunocompetent cells in ovarian follicles [5,7,43]. We assume that TLR-4 plays a significant role in recognition of SE to enhance IL-1β expression, leading to influx of immunocompetent cells.…”
Section: Discussionmentioning
confidence: 99%
“…T cell subsets play essential roles in the defense against viral and bacterial infection (Janse et al, 1994;Berndt and Methner, 2001;Beal et al, 2004), and CD4 + and CD8 + T cells were increased in hen oviduct infected by Salmonella enteritidis (Withanage et al, 1998(Withanage et al, , 2003. The current study showed that repeated stimulation by antigen increased the density of CD4 + , CD8…”
Section: Of B Cells and Macrophages By Cd4mentioning
confidence: 51%